2008
DOI: 10.1016/j.bbr.2008.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine withdrawal disrupts both foreground and background contextual fear conditioning but not pre-pulse inhibition of the acoustic startle response in C57BL/6 mice

Abstract: Nicotine withdrawal is associated with multiple symptoms such as anxiety, increased appetite, and disrupted cognition in humans. Although animal models have provided insights into the somatic and affective symptoms of nicotine withdrawal, less research has focused on the effects of nicotine withdrawal on cognition. Therefore, in this study, C57BL/6 mice were used to test the effects of withdrawal from chronic nicotine on foreground and background contextual fear conditioning, which present the context as a pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 86 publications
(126 reference statements)
3
40
0
Order By: Relevance
“…It is important to note that these plasma nicotine levels were within the range observed in smokers [5,64]. Additionally, withdrawal from chronic nicotine disrupts contextual but not cued conditioning [2,33,30,132,133], and this impairment in contextual learning can be ameliorated by nicotine replacement and by the smoking cessation drugs bupropion and varenicline [30,132,135]. Together, these data suggest that associations between stimuli and the effects of nicotine in humans may contribute to nicotine addiction, and these effects can be modeled in mice by studying the effects of nicotine on contextual learning.…”
Section: Nicotinic Acetylcholine Receptors: Animal Researchmentioning
confidence: 52%
“…It is important to note that these plasma nicotine levels were within the range observed in smokers [5,64]. Additionally, withdrawal from chronic nicotine disrupts contextual but not cued conditioning [2,33,30,132,133], and this impairment in contextual learning can be ameliorated by nicotine replacement and by the smoking cessation drugs bupropion and varenicline [30,132,135]. Together, these data suggest that associations between stimuli and the effects of nicotine in humans may contribute to nicotine addiction, and these effects can be modeled in mice by studying the effects of nicotine on contextual learning.…”
Section: Nicotinic Acetylcholine Receptors: Animal Researchmentioning
confidence: 52%
“…Our lab has previously demonstrated that withdrawal from chronic nicotine produces deficits in contextual learning (André et al, 2008; Davis, James, Siegel, & Gould, 2005; Gould et al, 2012; Portugal & Gould, 2009; Wilkinson & Gould, 2013; Wilkinson, Turner, Blendy, & Gould, 2013). In addition, we have found that galantamine (an AChE inhibitor and positive allosteric modulator of α4β2 nAChRs) can reverse deficits in contextual learning produced by withdrawal from chronic nicotine (Wilkinson & Gould, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…While the enhancing effects of acute nicotine are well documented, several studies have shown that while chronic nicotine has no effect on fear conditioning, withdrawal from chronic nicotine impairs contextual and trace fear conditioning (André, Gulick, Portugal, & Gould, 2008; Davis, James, Siegel, & Gould, 2005; Portugal & Gould, 2009; Portugal, Wilkinson, Kenney, Sullivan, & Gould, 2012; Raybuck & Gould, 2009). There is also evidence suggesting that during chronic nicotine administration, hippocampal nAChRs desensitize and upregulate and the resulting hypersensitive cholinergic system may be responsible for the effects of nicotine withdrawal on hippocampus-dependent learning (Dani & Heinemann, 1996; Gould et al, 2012; Marks, Grady, & Collins, 1993; Wilkinson & Gould, 2013).…”
Section: Involvement Of Nachrs In Anxiety and Anxiety Disordersmentioning
confidence: 99%